Development of an interface-oriented add-in modeling framework for integrated water system simulation and its application. (December 2020) - Zeng, Sidong; Du, Hong; Xia, Jun
Abstract: Integrated water system modeling is increasingly used to study the complex relationships between ecohydrological processes and the water-related social-economic systems. However, most of the traditional hydrological models are programmed in monolithic approach, which makes the model improvements or couplings for integrated simulation inconvenient for the inexperienced modelers. In this paper, we develop an interface-oriented add-in modeling framework (IAMF) to enable the water system models to be more reusable, extensible and flexible. The framework is designed using the interface-oriented add-in programming paradigm to provide a "plug-and-play" fashion. Meanwhile, parallel computing is supported easily of the framework based on water system network. We also develop a basic water system model consists of ecohydrological and water resources allocation, regulation modules to show how to develop model components using the framework. Then the model is used to simulate the natural-artificial water cycles in a case study irrigated area to evaluate its applicability as a modeling tool. Highlights: An interface-oriented add-in modeling framework (IAMF) is developed for water system modeling. Modules could be removed and added to the framework in a "plug-and-play" fashion. Parallel computing is easily supported based on the water system network. A water system model WEAR model is developed. A GIS-based GUI is developed allowing modeling in a user-friendly manner by "drag-and-drop".